Formulation of Local Ingredient-Based Fish Feed Containing 30% Protein Using the Pearson Square Method for Dumbo Catfish (Clarias gariepinus) Culture - Ester laoli; Ayu Damai kristiani zebua; Meisumarni Tafonao; Lesni Asniati Zalukhu; Vance Kristoper Angandowa Waruwu; Ratna Dewi Dewi Zebua; Betzy Victor Telaumbanua; Destriman Laoli (Fisheries Science Study Program, Faculty of Science and Technology, Muhammadiyah University of Sidenreng Rappang., 2026)
Feed formulation is the activity of designing and determining the proportions of various raw materials to meet specific nutritional requirements, particularly the protein content needed by fish or livestock to support growth and maintain health. In local ingredient based formulations, the components used generally come from plant, animal, and agricultural and fishery waste sources that are easily obtained and relatively affordable. This study applies the Pearson Square method in the formulation of artificial feed to achieve a protein content of 30%. Direct observations were then conducted on the fish's feed consumption response and growth parameter analysis to assess fish development during the rearing period. The objective of the study was to produce a locally sourced feed formulation with a 30% protein content for dumbo catfish (Clarias gariepinus) and evaluate its effect on fish response and growth. The results showed that feed formulated with a protein content of 30% provided a good feeding response and supported growth improvement, as indicated by the increase in length and survival rate until the end of the study. The use of local ingredients as a source of protein in this artificial feed is considered to have the potential to reduce production costs and support more efficient and sustainable catfish farming practices.